2014
DOI: 10.15380/2277-5706.jcsr.13.044
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system infections in the intensive care unit

Abstract: Burden of the problem Indian scenario Sparse published data are available on the spectrum of neurological infections requiring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…There are only few studies available from India with regard to the causative organisms and drug sensitivities of PCNSIs. [2,3,28] The present study demonstrated that the distribution of pathogens from our region was similar to the trend observed globally, thus helping the clinicians to choose the appropriate empirical antibiotic treatment for PCNSIs. The limitations of the study were that data with regard to clinical variables were not studied, the isolates included in the study may not be a representative for the whole of India, and the isolates were not characterized to molecular level to depict the resistance characteristics.…”
Section: Discussionsupporting
confidence: 77%
“…There are only few studies available from India with regard to the causative organisms and drug sensitivities of PCNSIs. [2,3,28] The present study demonstrated that the distribution of pathogens from our region was similar to the trend observed globally, thus helping the clinicians to choose the appropriate empirical antibiotic treatment for PCNSIs. The limitations of the study were that data with regard to clinical variables were not studied, the isolates included in the study may not be a representative for the whole of India, and the isolates were not characterized to molecular level to depict the resistance characteristics.…”
Section: Discussionsupporting
confidence: 77%
“…The best test to confirm CNS infection is the detection of pathogens in CSF culture [3,15]. This study included 68 (68.7%) positive CSF samples which had history of neurosurgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections have been known as the most common cause of the CNS infections, meanwhile fungi and mycobacteria are also frequently reported [3]. The pattern of pathogens recovered from CSF culture varies from Gram-positive cocci to multidrug-resistant Gram-negative bacteria depending on geographic region, age, co-morbidities, type of neurosurgical procedures, and site of infection [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation